PECULIARITIES OF THE COURSE OF COVID-19 IN SCHOOL-AGE CHILDREN AS A FUNCTION OF HUMORAL IMMUNITY AGAINST PERTUSSIS - Г. Павлишин; О. Панченко; К. Козак (Неонатологія, хірургія та перинатальна медицина, 2023)
Coronavirus disease remains one of the most serious diseases in the world. The percentage of severe and fatal cases in children is lower than in adults. The search for biomarkers of disease severity continues. There is evidence of heterologous immunity between the causative agent of coronavirus infection and some other infectious agents. Both Bordetella pertussis and SARS-CoV-2 cause damage to the respiratory system. It should be noted that the incubation period and transmission mechanism are similar for these two microorganisms. Pertussis vaccinations are given in childhood. The purpose of the study is to fi nd the charcteristics of the course of COVID-19 in school-aged children depending on the state of humoral immunity against pertussis toxin, assessing their level of immunoglobulin G against pertussis. Material and methods. 92 pediatric patients aged 6 to 17 years were studied, including 30 children without signs of the disease in the control group and 62 children with manifestations of laboratory- confi rmed COVID-19. The clinical features of the disease and laboratory indicators (C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), white blood cells, D-dimer) were evaluated, as well as the levels of free salivary cortisol and vitamin D. According to the severity of the disease, 3 groups were formed: the fi rst – 20 children with a mild course of COVID-19, the second – 33 patients with a moderate course of the disease, the third – 9 with a severe course of the disease. All children were tested for immunoglobulin G (Ig G) to pertussis toxin by enzyme- linked immunosorbent assay (VIROTECH B. pertussis PT Ig G ELISA, Rüsselsheim, Germany). The result was considered negative (no increase in the titer of specifi c class G antibodies to pertussis toxin), borderline, and positive (there is an increase in the titer of immunoglobulin G to pertussis toxin). Statistical analysis was performed using the program «Stat Plus» (Shapiro- Wilk test, mean  SD (standard deviation) with correct distribution of characteristics; median, upper and lower quartiles with incorrect distribution, Chi-square test, Man-Whitney test, Fisher’s test). The study was conducted in accordance with the rules of patient safety and ethical principles of scientifi c medical research involving human subjects (2000). The permission to conduct this study was given by the Bioethics Commission (Protocol No. 61 of 13.11.2020). The parents (legal representatives) of the patients gave their written consent to the conduct of this study. This study is a fragment of research work «An Integrated Approach to Symptom Control, Long- Term Prognosis in the Context of Comorbid Pathology in the Clinic of Internal Diseases and Family Doctor Practice» (state registration No. 0118U000361). Results. The mean age of the patients was 11.573.82 years. The study groups did not diff er in sex (x2=4.97, p=0.174) and age (p=0.490) composition. The level of humoral immunity against pertussis toxin diff ered signifi cantly between the study groups. A positive and borderline result for the presence of specifi c immunoglobulin G to tetanus toxin was found in 75.86 % of children without signs of disease. At the same time, only 41.51 % of children with COVID-19 manifestations had a positive and borderline result (p=0.005). A positive and borderline result for the presence of specifi c immunoglobulin G to tetanus toxin was seen in 66.67 % of children with mild infection, 33.33 % of patients with moderate disease, and only 12.50 % of patients with severe disease (X2=16.91, P=<0.001). Children with a negative result for immunoglobulin G to pertussis toxin have signifi cantly higher WBC count (1.3-fold), ESR (2.4-fold), D-dimer (3.4-fold), and CRP (1.5-fold) compared to patients with positive and borderline levels of these antibodies. In children with a negative result, there was a 6.25-fold increase in salivary free cortisol (p<0.001) and a 2.0-fold decrease in vitamin D levels (p<0.001). Conclusions. In children with COVID-19 manifestations, there was a signifi cantly higher percentage of negative test results for the presence of IgG to pertussis toxin compared to the control group, indicating a lower level of humoral immunity to tetanus in this group of patients. In children with mild disease, there was a signifi cantly higher percentage of positive and borderline test results for the presence of IgG to pertussis toxin (indicating a higher level of humoral immunity against this pathogen) compared to the groups of children with moderate and severe disease. The absence of specifi c immunoglobulins G to pertussis toxin is associated with an increase in the level of pro-infl ammatory markers (leukocyte count, ESR, CRP) and D-dimer, which also indicates a more severe course of COVID-19. Patients who are negative for pertussis toxin antibodies have elevated cortisol levels as a marker of stress and decreased vitamin D levels. Both biologically active substances are involved in the immune response to infectious agents and may serve as additional non-specifi c markers of COVID-19 severity. Therefore, low humoral immunity to pertussis contributes to the increase in COVID-19 severity in childhood.